The Role of Obesity in Pediatric Orthopedics. (May 2019) - Nowicki, Philip; Kemppainen, John; Maskill, Lisa; Cassidy, Jeffrey
Abstract : Pediatric obesity has become a worldwide epidemic and leads to notable effects on the developing skeleton that can have lifelong implications. Obesity in the pediatric population alters bone metabolism, increasing the risk for fracture. It can alter the presentation of common pediatric orthopaedic conditions such as scoliosis. Obesity also leads to changes in the patterns and severity of pediatric fractures as well as alters conservative fracture treatment due to increased displacement risk. Obese pediatric trauma patients place a high burden on the nationwide hospital system in a variety of ways including the increased risk of perioperative complications. Obesity is modifiable, and addressing the issue can improve the orthopaedic and overall health of children.